Microstructure characterisation of titanium alloy manufactured with selective laser melting - Tan, Boon Piao (2015)
Ti-6Al-4V is also known as the “workhorse” of the titanium metals as it is the most commonly used titanium alloy, accounting for more than 50% of entire titanium applications. It is commonly used for aerospace applications such as airframe components and turbine engines’ fan blades.Recent developments in additive manufacturing have allowed complex parts made from metal alloys to be manufactured in a short time. This project seeks to investigate the microstructural features of titanium alloy produced by additive manufacturing, specifically using the process of selective laser melting and how they differ with conventionally produced titanium alloy.